Unılateral Contracts - Jugeli, Tea (European Scientific Journal, ESJ, 2017)
Origin of the relations deriving from the law of obligations is grouped primarily according to the voluntary and involuntary grounds. Agreements and unilateral contracts are among the obligations emerged on the basis of demonstration of the will (intent). It is very difficult to find materials on unilateral contracts in the Georgian legal literature; however, analysis of the Georgian judicial practice proves that currently this is a challenging issue and it is important to conduct studies on it. The concept of unilateral contract does not imply the necessary fulfilment of the intent demonstrated by one person. It is necessary this unilaterally demonstrated intent be accepted by the other party. The phrase ‘unilateral contract’ and ‘unilateral demonstration of intent’ do not have identical meanings and therefore, it is a mistake to use them as synonyms. Unilateral agreements in the French law are the so called incomplete bilateral agreements where their bilaterality is hindered by the lack of the elements of bilateral agreements at the moment of concluding such an agreement – and specificity of such agreements should be taken into account during legal proceedings. The existence of nonhomogeneous judicial practice regarding unilateral contracts and agreements clearly proves that it is necessary to conduct further research in this field and also to ensure detailed simplification of legislative norms as well.